Overtures (Prometheus, Egmont, and Leonore no. 3) arranged for quintet or sextet - Beethoven, Ludwig van, 1770-1827:::Creator::::::::::::; Masi, G. (Girolamo):::Contributor:::::::::::: (London; Monzani & Hill; United Kingdom, 2024)
Arrangement by Girolamo Masi of the Overtures for Prometheus (op. 43), Egmont (op. 84), and Leonore no. 3 for two violins, viola, cello, flute, and an optional piano or bass part.